In the unlikely event ebook - Blume, Judy (2015)
NATIONAL BESTSELLER • The author of Are you There God? It’s Me, Margaret returns with an adult novel that takes us back to the 1950s and introduces us to the town where she herself grew up, where a community is left reeling after a real-life tragedy when a series of airplanes fell out of the sky. “Makes us feel the pure shock and wonder of living.... Judy Blume isn’t just revered, she’s revolutionary.” — The New York Times Book Review “No one captures coming-of-age milestones…like Blume.” — The Boston Globe Here she imagines and weaves together a vivid portrait of three generations of families, friends, and strangers, whose lives are profoundly changed during one winter. At the center of an extraordinary cast of characters are fifteen-year-old Miri Ammerman and her spirited single mother, Rusty. Their warm and resonant stories are set against the backdrop of an extraordinary real-world tragedy. Gripping, authentic, and unforgettable, In the Unlikely Event has all the hallmarks of this renowned author’s deft narrative magic.